2021
DOI: 10.3389/fimmu.2021.681714
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Profile in Whole Blood of Patients With Chronic Spontaneous Urticaria

Abstract: BackgroundChronic spontaneous urticaria (CSU) is a common autoimmune skin disease. Little is known about the role of epigenetics in the pathogenesis of CSU. This study aimed to investigate genome-wide DNA methylation profile in whole blood of patients with CSU.Patients and MethodsGenome-wide DNA methylation levels in whole blood samples of 95 Chinese Han ethnicity adult CSU patients and 95 ethnicity-, age- and sex-matched healthy controls were analyzed using Illumina 850K methylation chip. The differentially m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Subsequently, past research has demonstrated that the distribution of DMPs within the promoter region varies across diseases. In autoimmune diseases, a predominant characteristic is hypomethylated sites in the promoter region DMPs (16,17), a finding that is reinforced by our research. Contrastingly, in carcinoma, hypermethylated sites are more prevalent within promoter region DMPs (18,19).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Subsequently, past research has demonstrated that the distribution of DMPs within the promoter region varies across diseases. In autoimmune diseases, a predominant characteristic is hypomethylated sites in the promoter region DMPs (16,17), a finding that is reinforced by our research. Contrastingly, in carcinoma, hypermethylated sites are more prevalent within promoter region DMPs (18,19).…”
Section: Discussionsupporting
confidence: 82%
“…Further, DMPs with DNAm levels exceeding 0.7 or falling below 0.3 were selected, as such extreme levels are more likely indicative of lost expression or abundant expression. This approach aids in the discovery of potential biomarkers with functional relevance to disease phenotypes (16). Lastly, prior research has established that methylation patterns of multiple DMPs on promoters constitute key mechanisms influencing gene expression (15).…”
Section: Discussionmentioning
confidence: 99%
“…The data of genome-wide DNA methylation profile of the AR patients were available at GEO database ( ; GSE50222, n = 32, AR during pollen season = 8, AR outside pollen season = 8, healthy control =16) ( 37 ). The data of genome-wide DNA methylation profile of the CSU patients were available at National Genomics Data Center (NGDC) database ( ; OEP002482, n = 190, CSU = 95, healthy control = 95) ( 34 ). Our workflow for bioinformatics analysis of publicly available datasets from both the GEO and NGDC databases is illustrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Current research suggested that it may contribute to a variety of cytological processes of T cells in different allergic diseases, including Treg deficiency, TH1 and TH2 polarization, and differentiation of CD4+ T cells (30)(31)(32). Interestingly, researchers have found that some allergic responses of AR or CSU patients can be predicted by the DNA methylation levels when exposed to grass pollen (33,34). In conclusion, the above results indicated that pollen can affect DNA methylation in comorbidity patients, potentially regulating the biological functions of T cells.…”
Section: Introductionmentioning
confidence: 99%